Afrocentric leadership coaching among Shona men in Zimbabwe - Mhlanga, Brian Ndabaningi (My University, 2020)
This study looks at the need for an African approach to leadership coaching. It aims to contribute towards a leadership coaching model that is Afrocentric or is framed around the African concept of “Ubuntu”. Leadership coaching is a profession that is widely practiced and yet has limited scientific theory. Practitioners on the African continent rely heavily on the Eurocentric philosophical approaches to leadership coaching without taking cognizance of cultural considerations among other things. Using the social identity theory, and a case study of Zimbabwe Shona male executives will be conducted on selected Shona cultural aspects on leadership and how gender, spirituality, socioeconomic and political factors have impacted on leadership coaching. The tools used for data collection included observations and interviews (semi-structured face-to-face). The target population comprised eight Shona male executives and four leadership coaches working in the provinces of Mashonaland East and West, Harare and Midlands, Zimbabwe. Data collected for this study is qualitative and was interpreted using QSRNVIVO in uncovering emerging themes, patterns and insights. The findings of the study reveal that the Shona traditional ways of healing are appropriate and can be integrated into western and modern leadership coaching. The study also established coaching in Zimbabwe among Shona men is perceived to be a western leadership development tool and fails to embrace African spiritual consciousness sufficiently. The study gives an understanding of how Shona men understand and experience leadership mastery revealing the need to accommodate some of the Shona aspects of culture to leadership coaching. Insights from this exploration will contribute towards the formulation of an Ubuntu Leadership Coaching model that could add value to leadership coaching not only in Zimbabwe but potentially across the continent.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Business Executive Coaching to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2020
Keywords: Afrocentric; Masculinity; Ethnicity; Gender; Zimbabwe; Inter-cultural coaching; SDG-8: Decent work and economic growth